MENINGKATKAN KOMPETENSI GURU DALAM PEMBELAJARAN DI MADRASAH ALIYAH DENGAN MELALUI LESSON STUDY - Asep Ikin Sugandi; Rippi Maya (IKIP SILIWANGI, 2020)
The purpose of this service is to increase teacher competency in learning in Madrasah Aliyah through lesson study. The Dedication Method used is qualitative descriptive. This dedication took place in Madrasah Aliyah Assa'idiyyah Cipanas Cianjur Regency 2019-2020 Academic Year. The instrument used in this study was a questionnaire to determine student responses to learning using Lesson Study and. The results of the study show that Lesson Study can increase students' learning activities and can improve teacher competency in learning.